Blended Phenotype of Silver-Russell Syndrome and SPG50 Caused by Maternal Isodisomy of Chromosome 7. (February 2021) - Ziegler, Marvin; Russell, Bianca E.; Eberhardt, Kathrin; Geisel, Gregory; D'Amore, Angelica; Sahin, Mustafa; Kornblum, Harley I.; Ebrahimi-Fakhari, Darius
Abstract : Objective: Uniparental isodisomy can lead to blended phenotypes of imprinting disorders and autosomal recessive diseases. To determine whether a complex neurodevelopmental disorder was caused by uniparental isodisomy, a detailed clinical and molecular characterization was performed. Methods: A combination of clinical, molecular, and imaging data and functional studies in patient-derived fibroblasts. Results: We report a 4-year-old female with a blended, complex phenotype of Silver-Russell syndrome (SRS) and hereditary spastic paraplegia type 50 (SPG50) caused by total maternal isodisomy of chromosome 7 (UPiD(7)mat) and a loss-of-function variant in AP4M1 (NM_00472.3: c.59-1G>C, IVS1-1G>C). Functional studies in patient-derived fibroblasts confirmed the loss of adaptor protein complex 4 function. Distinctive facial features, intrauterine growth restriction, short stature, feeding difficulties, and severe gastroesophageal reflux were consistent with SRS. Features associated with SPG50 included early-onset epilepsy, episodes of stereotypical laughter, and thinning of the corpus callosum and ventriculomegaly on brain MRI. Symptoms shared by both syndromes such as developmental delay, short stature, and axial and appendicular hypotonia were also present. Notably, other common manifestations of SPG50 such as microcephaly or spasticity had not developed yet. Conclusions: This case highlights that atypical clinical features in patients with well-described imprinting disorders should lead to investigations for recessive conditions caused by variants in genes that localize to the region of homozygosity.